ANALISIS PENERAPAN LITERASI DIGITAL UNTUK MENINGKATKAN KETERAMPILAN BERBAHASA INDONESIA DI SEKOLAH DASAR - Nisrina Hisanah; Ahmad Nurefendi Fradana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Digital literacy is an important thing in the current digital era, one of which is helping improve Indonesian language skills, especially in elementary schools. So digital-based learning needs to be implemented for students to answer the challenges of the current digital era and help teachers in carrying out the learning process. This research aims to explore how digital literacy can be applied in elementary schools to improve Indonesian language skills. The research method used was descriptive qualitative with interview and observation instruments involving class teachers and class IV students at SDN Jatijejer. The data collection process was carried out by interviewing class teachers to find out the extent to which digital literacy can be applied in the classroom. Observations were carried out by directly observing students' interactions with digital technology in order to improve their Indonesian language skills. It is hoped that the results of this research will provide insight for readers to support digital literacy and Indonesian language skills as well as support active, effective and creative Indonesian language learning.